1997
DOI: 10.1111/1468-2257.00070
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of Retail Businesses

Abstract: Previous studies employing the trade area analysis procedure of pull factors assume retail sectors are independent. However, interdependencies exist between and among retail sectors. Employing a multivariate Tobit procedure, the agglomerative aspects of retail trade can be captured. Results indictate that interdependencies exist between retail sectors and if these retail interdependencies are ignored, extension and outreach retail sector programs may prove to be ineffective.and 108 Cowley Rd., Oxford, OX4 lJF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Demand threshold analyses seek to identify the minimum population required for an establishment within a particular industry to earn a su cient rate of return to stay in business (Berry & Garrison, 1958a, 1958bHarris & Shonkwiler, 1997;Parr & Denike, 2016;Shaffer et al, 2004). Derivates of demand threshold analysis, such as Bresnahan and Reiss's (1991) "entry thresholds" for retail rms or Cleary et al's (2019) "breakeven market sizes" for food hubs use ordered probits to identify local conditions that in uence the number of rms in a market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Demand threshold analyses seek to identify the minimum population required for an establishment within a particular industry to earn a su cient rate of return to stay in business (Berry & Garrison, 1958a, 1958bHarris & Shonkwiler, 1997;Parr & Denike, 2016;Shaffer et al, 2004). Derivates of demand threshold analysis, such as Bresnahan and Reiss's (1991) "entry thresholds" for retail rms or Cleary et al's (2019) "breakeven market sizes" for food hubs use ordered probits to identify local conditions that in uence the number of rms in a market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…6 The extreme rural conditions in many of the sampled counties suggest that consumers may shop at local Wal-Mart locations instead of traveling to more urban areas. This pull-factor effect attracts more local retail trade (Stone 1997;Harris and Shonkwiler 1997).…”
Section: Data and Estimationmentioning
confidence: 99%
“…Stone's (1997) comparative study of 34 towns (5,000-40,000 pop.) examined changes in the same sets of variables as did the earlier studies, examining a metric known as the pull factor (the proportion of sales in a county as a proportion of statewide sales) in several industry sectors (see Harris and Shonkwiler 1997 for a review of the literature). The short-run effects pointed to Wal-Mart-induced increases (or slower decreases) in several sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Thill's seminal models (1986Thill's seminal models ( , 1992 incorporated the likely importance of multi-stop shopping in retail viability. Shonkwiler and Harris (1996) and Harris and Shonkwiler (1997) evaluated the importance of such multi-purpose shopping by empirically testing this sectoral interdependence. They found that certain retail establishments in a place are dependent on other retail activities in the place.…”
Section: Introductionmentioning
confidence: 99%